Toad Glandular Secretions and Skin Extractions as Anti-Inflammatory and Anticancer Agents. (6th March 2014) - Qi, Ji; Tan, C. K.; Hashimi, Saeed M.; Zulfiker, Abu Hasanat Md.; Good, David; Wei, Ming Q.
Abstract : Toad glandular secretions and skin extractions contain many natural agents which may provide a unique resource for novel drug development. The dried secretion from the auricular and skin glands of Chinese toad ( Bufo bufo gargarizans ) is named Chansu, which has been used in Traditional Chinese Medicine (TCM) for treating infection and inflammation for hundreds of years. The sterilized hot water extraction of dried toad skin is named Huachansu (Cinobufacini) which was developed for treating hepatitis B virus (HBV) and several types of cancers. However, the mechanisms of action of Chansu, Huachansu, and their constituents within are not well reported. Existing studies have suggested that their anti-inflammation and anticancer potential were via targeting Nuclear Factor (NF)-κ B and its signalling pathways which are crucial hallmarks of inflammation and cancer in various experimental models. Here, we review some current studies of Chansu, Huachansu, and their compounds in terms of their use as both anti-inflammatory and anticancer agents. We also explored the potential use of toad glandular secretions and skin extractions as alternate resources for treating human cancers in combinational therapies.